The Determinants of Capital Structure: Empirical evidence from Thai Banks - Allen, David E.; ., Robert John Powell (Information Management and Business Review, 2013)
The aim of this study is to examine the determinants of the capital structure of Thai banks. The data spans a ten year period from 1999 – 2008. The differentiation point of this study is that, whereas most studies on capital structure focus predominantly on internal bank variables, this study, in addition to internal variables includes market-based risk variables. A range of market-based default and value at risk variables were considered which were then narrowed down to improve the model. Fixed effects panel data analysis is employed, with both market and book leverage used as dependent variables. The Thai bank study is benchmarked to Japanese and Malaysian banks. The study found that the significance of the market-based variables is greater for market leverage than for book leverage. The results can assist regulators and banks in understanding the impact of different market and internal variables on capital.